The Digital Divide Exacerbates Disparities in Latinx Recruitment for Alzheimer’s Disease and Related Dementias Online Education During COVID-19 - Ángela Gutiérrez PhD, MPH; Rosalba Cain; Nadine Diaz DSW, MSW; María P. Aranda PhD, MSW, MPA, LCSW (Gerontology and Geriatric Medicine, 2022)
Latinx adults experience a high burden of dementia. Given that modifiable factors drive dementia disparities, engaging Latinxs in Alzheimer’s disease and related dementias (ADRD) education is critical to address dementia burden among this aging population. Yet, no studies have documented the role of the COVID-19 pandemic on dementia education among Latinxs. This study: (1) elucidates the recruitment and retention processes targeting Latinxs for online educational events during the pandemic; (2) describes facilitators/barriers to participation; and (3) offers lessons learned. We developed online dementia-focused workshops (English and Spanish) and employed a cold-calling approach to invite Latinx participants enrolled in clinical studies ( N = 209). Bivariate tests assessed demographic and cognitive differences between those who recruiters did ( n = 60) and did not ( n = 149) successfully engage. Frequency counts assessed participants’ technological access. Only 8/209 attended the online events; all held university degrees, most reported English as their primary language, and none experienced cognitive impairment. Results underscore how educational attainment, cognitive impairment, language preference, and age intersect to shape recruitment in dementia-focused online education. To promote healthy aging and to ameliorate dementia disparities, barriers to online engagement among older Spanish-speaking Latinxs with cognitive impairment and low educational attainment must be addressed.